Social and Emotional Learning Difficulties of Refugee High School Students in an After-School Tutoring Program - Xu, Xiaofei; Zhu, Xibei; Zhou, George (Social Education Research, 2026)
School-aged children constitute a significant portion of the large number of refugees that have resettled in Canada in recent years. Due to the lack of cross-cultural competencies, a social justice focus, and transformative leadership skills, Canadian schools are often challenged to address refugee students’ socio-psychological problems effectively. To help with the issue, this study examined 8 refugee high school students through an after-school tutoring program and evaluated their performances in the five domains of social-emotional learning competencies. Findings of the study reveal that refugee students’ performance in these skills is not optimal in general. Especially, there is a high demand in improving the refugee students’ self-awareness, self-management, and responsible decision-making. Implications of our findings for school instructors and policy makers are highlighted.